Modifying Interpretation and Imagination in Clinical Depression: A Single Case Series Using Cognitive Bias Modification - Blackwell, SE; Holmes, E (2010)
The current cognitive bias modification (CBM) paradigm targets interpretation bias (CBM-I) in depression via promoting positive imagery. We investigated the impact of repeated sessions of this CBM-I on interpretation bias, mood and mental health in participants currently experiencing a major depressive episode. Seven participants completed daily sessions of CBM-I at home for one week in a single case series. Outcome measures were completed pre and post a one-week baseline period, and after the week of daily CBM-I. Depressive symptoms were also assessed at a 2-week follow-up. Four of seven participants demonstrated improvements in mood, bias and/or mental health after one week of CBM-I, with improvements in depressive symptoms maintained at follow-up. Discussion of the remaining three highlights difficulties involved in translating CBM-I interventions from the laboratory to the clinic. To bridge this gap, we suggest that it is critical to examine the failures as well as the successes. © 2010 John Wiley and Sons, Ltd.